Pembelajaran Berbasis Modul Filsafat Bahasa di STKIP PGRI Pacitan - Agoes Hendriyanto; sugeng suryanto (LPPM Press, 2016)
One of the most important keys of the university advancement in Indonesia is thecompetitive grant research scheme. As one of that mentioned research scheme, thisresearch had been the second year to accomplish. The purpose of this Researchand Development (R&D) was to enhance the competence of students using themodule of scientific language philosophy. This research was carried out from 2016on Indonesian Literature and Language Education Study program in STKIP PGRIIndonesia Pacitan up to 2017. The research consisted of 12 meetings within 4 trialsusing the single one-shot case study experimental method. This method aimedat revealing the effect of the local wisdom-based scientific language philosophymodules toward language competence. The research findings showed that theresult of the first test compared to the second test was t12 = 2.77 ≤ t table 2,021 withinthe degrees of freedom 38 which meant that the language competence had beenincreased. Furthermore, the second test compared to the third test was t23 =2.88≤ ttable 2,021 within the degrees of freedom 38. Finally, the third test comparedto the fourth test result was t34 = 2.79 ≤ t table 2,021. Based on t test results, it canbe inferred that the module of scientific language philosophy based on the localwisdom is effective to increase the language competence.